Implicit theories of criminal behavior: fostering public support for ex-offender community reentry - Rade, Candalyn B. (Applied psychology in criminal justice, 2018)
Ex-offenders face many barriers during the process of community reentry, including difficulty obtaining housing or employment. These barriers are often the result of stigma and discrimination that can negatively affect domains of functioning and well-being that are central to successful reintegration. Implicit theory suggests that stigmatizing attitudes may be explained through beliefs regarding the invariable (fixed mindset) or malleable (growth mindset) nature of human attributes. Prior work demonstrated how these mindsets can explain attitudes toward ex-offenders and support for community reentry. In this manuscript, we report on two studies that examined whether attitudes toward ex-offenders and support for their reentry can be influenced through a brief mindset-based persuasive reading. In Study 1, we piloted a brief, experimental manipulation among a student sample (n = 352) to induce growth mindsets regarding criminal behavior to foster positive attitudes toward ex-offenders and their reentry. In Study 2, we replicated the first study in a community-based sample (n = 451) and tested ex-offender race as a potential moderator. Mediation analyses demonstrated a causal pathway between mindset condition, attitudes toward ex-offenders, and support for reentry, and provided empirical evidence that the mindset-based experimental manipulation can foster growth mindsets and support for ex-offender community reentry, regardless of ex-offender race. Findings present directions for developing a potentially low-cost and time-effective strategy that can be disseminated easily through online or other media platforms, and tailored to target specific barriers to reentry. Further research is needed to establish the persistence of effects on attitudinal changes over time.